Rapid multiplex PCR for respiratory viruses reduces time to result and improves clinical care: Results of a systematic review and meta-analysis. Issue 5 (May 2023) - Clark, Tristan W.; Lindsley, Kristina; Wigmosta, Tara B.; Bhagat, Anil; Hemmert, Rachael B.; Uyei, Jennifer; Timbrook, Tristan T.
Summary: Objectives: The clinical impact of rapid sample-to-answer "syndromic" multiplex polymerase chain reaction (PCR) testing for respiratory viruses is not clearly established. We performed a systematic literature review and meta-analysis to evaluate this impact for patients with possible acute respiratory tract infection in the hospital setting. Methods: We searched EMBASE, MEDLINE, and Cochrane databases from 2012 to present and conference proceedings from 2021 for studies comparing clinical impact outcomes between multiplex PCR testing and standard testing. Results: Twenty-seven studies with 17, 321 patient encounters were included in this review. Rapid multiplex PCR testing was associated with a reduction of − 24.22 h (95% CI −28.70 to −19.74 h) in the time to results. Hospital length of stay was decreased by −0.82 days (95% CI −1.52 to −0.11 days). Among influenza positive patients, antivirals were more likely to be given (RR 1.25, 95% CI 1.06–1.48) and appropriate infection control facility use was more common with rapid multiplex PCR testing (RR 1.55, 95% CI 1.16–2.07). Conclusions: Our systematic review and meta-analysis demonstrates a reduction in time to results and length of stay for patients overall along with improvements in appropriate antiviral and infection control management among influenza-positive patients. This evidence supports the routine use of rapid sample-to-answer multiplex PCR testing for respiratory viruses in the hospital setting. Highlights: The clinical impact of rapid multiplex testing for respiratory viruses is not known. This meta-analysis of 27 studies evaluates the impact compared with standard testing. Rapid multiplex testing was associated with reduced time to results and length of stay. Rapid multiplex testing improved antiviral use and infection control in influenza patients. These results support rapid multiplex PCR tests in suspected respiratory infections.